METHODOLOGICAL FRAMEWORK FOR STUDYING SUSTAINABLE DEVELOPMENT IN ECONOMIC SYSTEMS - Lopatynskyi, Yurii; Burynskyi, Volodymyr (Current Problems of Sustainable Development, 2026)
The article examines the methodological foundations of research on sustainable development in economic systems, proceeding from the observed fragmentation of contemporary scientific approaches. The systems approach, ESG-oriented assessment, the SDG-based framework, and the institutional perspective each capture distinct dimensions of sustainable development yet are typically applied in isolation – a pattern that undermines analytical consistency and limits the comparability of research outcomes. This fragmentation manifests as a persistent gap between conceptual interpretations of sustainable development and the instruments available for its empirical analysis; it is further reinforced by insufficient coherence across levels of analysis and by the limited integration of institutional factors. Together, these limitations point to the need for the structured integration of existing approaches rather than their further proliferation. Rather than extending the existing repertoire of approaches, the study treats such integration as a primary methodological task. To this end, a methodological framework for studying sustainable development
Keywords: sustainable development; economic systems; research methodology; methodological framework; ESG; Sustainable Development Goals; institutional approach; levels of analysis; analytical tools